Deactivation of the inferior colliculus by cooling demonstrates intercollicular modulation of neuronal activity - Orton, Llwyd D.; Poon, Paul W.; Rees, Adrian (Frontiers in Neural Circuits, 2012)
The auditory pathways coursing through the brainstem are organised bilaterally in mirror image about the midline and at several levels the two sides are interconnected. One of the most prominent points of interconnection is the commissure of the inferior colliculus (CoIC). Anatomical studies have revealed that these fibres make reciprocal connections which follow the tonotopic organisation of the inferior colliculus (IC), and that the commissure contains both excitatory and, albeit fewer, inhibitory fibres. The role of these connections in sound processing is largely unknown. Here we describe a method to address this question in the anaesthetised guinea pig. We used a cryoloop placed on one IC to produce reversible deactivation while recording electrophysiological responses to sounds in both ICs. We recorded single units, multi-unit clusters and local field potentials (LFPs) before, during and after cooling. The degree and spread of cooling was measured with a thermocouple placed in the IC and other auditory structures. Cooling sufficient to eliminate firing was restricted to the IC contacted by the cryoloop. The temperature of other auditory brainstem structures, including the contralateral IC and the cochlea were minimally affected. Cooling below 20 °C reduced or eliminated the firing of action potentials in frequency laminae at depths corresponding to characteristic frequencies up to 8 kHz. Modulation of neural activity also occurred in the un-cooled IC with changes in single unit firing and LFPs. Components of LFPs signalling lemniscal afferent input to the IC showed little change in amplitude or latency with cooling, whereas the later components, which likely reflect inter- and intra-collicular processing, showed marked changes in form and amplitude. We conclude that the cryoloop is an effective method of selectively deactivating one IC in guinea pig, and demonstrate that auditory processing in the IC is strongly influenced by the other.